2019
DOI: 10.1155/2019/6924191
|View full text |Cite
|
Sign up to set email alerts
|

Pachychoroid Pigment Epitheliopathy and Choroidal Thickness Changes in Coeliac Disease

Abstract: Purpose. To evaluate choroidal thickness in patients with coeliac disease (CD) using spectral domain optical coherence tomography (SD-OCT) and to compare the results to normal eyes. Methods. Seventy patients with CD and 70 healthy controls were included in this prospective, comparative study. All participants underwent a complete ophthalmologic evaluation and SD-OCT. Subfoveal, nasal (nasal distance to fovea 500 μm, 1000 μm, and 1500 μm), and temporal (temporal distance to fovea 500 μm, 1000 μm, and 1500 μm) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Choroidal thicknesses of eyes with pachychoroid phenotype that were greater than 300 μm, with and without retina pigment epithelium abnormalities, were evaluated as PPE and uncomplicated pachychoroid epitheliopathy (UCP), respectively [12].…”
Section: Methodsmentioning
confidence: 99%
“…Choroidal thicknesses of eyes with pachychoroid phenotype that were greater than 300 μm, with and without retina pigment epithelium abnormalities, were evaluated as PPE and uncomplicated pachychoroid epitheliopathy (UCP), respectively [12].…”
Section: Methodsmentioning
confidence: 99%
“…Choroidal thicknesses of eyes with pachychoroid phenotype are greater than 300 μm together with and without retina pigment epithelium abnormalities were evaluated as uncomplicated pachychoroid (UCP) and pachychoroid pigment epitheliopathy (PPE) respectively [12].…”
Section: Methodsmentioning
confidence: 99%
“…Ocular findings due to CD occupy an important place among these extraintestinal findings because of the direct effect of visual function and ocular comfort on quality of life. [5][6][7] Bölükbaşı et al has revealed that mean CT measurements at all seven areas of subfoveal, nasal, and temporal points were found to be higher in the adult celiac group. 15 There is only one study by Dogan et al that have found insignificant decrease in thickness of choroid in pediatric CD patients at only subfoveal area.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Bölükbaşı et al has revealed that mean CT measurements at all seven areas of subfoveal, nasal, and temporal points were found to be higher in the adult celiac group. 15 There is only one study by Dogan et al that have found insignificant decrease in thickness of choroid in pediatric CD patients at only subfoveal area. The studies about eye involvement and effect of gluten free diet on ocular findings in CD patients are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation